Children’s Games and Adult Repentance: Concept of Childhood in Literature of Early 20th Century - N. E. Seibel (Научный диалог)
This article describes the transformation of the image of the child in literature during the 10-30s of the 20th century. The stories of three contemporary authors are used as material, which are connected by motifs of enlightenment and repentance: “The Day of the Boy” by F. Verfel, “The Paper Kite” by Lu Xin, and “On Tenderness” by Nadezhda Teffi. The basis for comparative analysis is the biographical similarities, close circle of philosophical and aesthetic interests of Austrian, Chinese, and Russian authors, as well as the genre and thematic proximity of the texts. The researcher assumes that increased attention to the image of the child arises in the early 19th century in Romantic literature, which interprets it either as a victim or as an angel. However, in the second half of the 19th century, images of “evil children” begin to appear. The analysis shows that under the influence of Freud, the motive of children’s games as a way to familiarize oneself with evil, temptation, and inevitable experiences during development consistently emerges in literature of the early 20th century. The common form of reminiscence present in all three texts allows the authors to interpret childhood events causally and derive later moral experiences from children’s games. The article concludes that Verfel’s, Lu Xin’s, and Teffi’s stories are influenced by Freud’s idea of the interconnection between childhood impressions and the fate of adults, who must comprehend past shame, guilt, and repentance.